What Makes Islamic Microfinance Islamic? A Case of Indonesia’s Bayt al-Māl wa al-Tamwīl - Hyung-Jun Kim; Bambang Hudayana (Studia Islamika, 2022)
This article highlights the weaknesses in the formalistic approach to Islamic finance which deals mainly with shariah compliance. This research examines religious elements  that consist in the operations of the Indonesian Islamic microfinance institution by criticizing it for the costs of transactions, the composition of contracts, and the procedures for murābaḥah (working capital finance). Acknowledging that shariah principles were compromised  to some extent, the BMT’s employees did not question the Islamic character and identity of the BMT.  Highlighting their commitments to improving the economic conditions of the Muslim community, active involvement in charity and socio-religious works, business practices caring for the unfortunate people, and their Islamic networks, the employees believe that the BMT has implemented Islamic values. For them, Islamic finance is not only attributed to sharia compliance, but it must also contain a wide range of religious tendencies and practices. By stressing the importance of the aspirations and commitments of Muslim activists, this paper widens the discussion of how to vitalize Islamic finance.